Beyond the precepts : the relevance of ethics to mindfulness based interventions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Trevathan, Penelope (Massey University, 2023)
Mindfulness-based interventions (MBIs) are derived from Buddhism and have proliferated in modern society to enhance the psychological well-being of individuals. However, there has been concerns about the omission of ethical training, which is foundational to Buddhist conceptualizations of mindfulness. The reinstatement of ethics has the potential to enhance MBIs and mitigate these concerns but may not be relevant to a modern audience and a scientific epistemology. Western monastics whose lives traverse both traditional Buddhist practices and western frames of reference are uniquely positioned to explore Buddhist ethics and add insight to this dialogue. Prospective participants (n=7) were purposively selected from Buddhist monasteries in Aotearoa/New Zealand and participated in a semi-structured interview that elucidated the lived experience of Buddhist ethics and monastics' perspectives on the relevance of Buddhist ethics for western people and MBIs. An Interpretative Phenomenological Analysis (IPA) resulted in six group experiential themes: Ethical training as a determinant of transformation; The psychospiritual benefits of ethical maturation; Barriers to ethical engagement; Where psychology diverges; Ethics meets the deeper needs of modern people and MBIs; Proposed adaptations to the presentation of Buddhist ethics. These were encapsulated in the overarching theme: An orientation towards flourishing and fulfilment. The participants’ narratives functioned to demystify ethics and outlined conceptualizations of ethics beyond the precepts, where ethics as an orientation towards collective flourishing through self-enquiry could support MBIs as a prophylaxis against the multitudinous psychological, relational, and societal harms that are the consequences of unethical behaviours to meet the deeper transformational needs of society.
Keywords: 520406 Sensory processes, perception and performance